2006
DOI: 10.1080/09540120600581460
|View full text |Cite
|
Sign up to set email alerts
|

Growing up: Perspectives of children, families and service providers regarding the needs of older children with perinatally-acquired HIV

Abstract: Children with perinatally-acquired HIV are living into adolescence and adulthood. As this is a relatively new phenomenon, there is a paucity of research highlighting the complex issues that arise for these children. This qualitative case-study examines the needs of a select group of older children (9-16 years old) with perinatally-acquired HIV in the province of British Columbia, Canada through focus groups and interviews conducted with ten HIV-infected children, 11 family members and 11 service providers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 15 publications
3
57
0
1
Order By: Relevance
“…All participants were at the age at which sex and sexuality were important issues and they were aware of the difficulties that disclosure of their status might pose to potential partners. Receiving positive, encouraging and normalising messages about their sexuality and sexual behaviour is important in order that positive young people do not grow up with negative feelings about themselves, sex and sexuality (Fielden et al, 2006;Campbell et al, 2009). Interestingly, participants did not comment on the specific sexual health components of the LFP which included experience of handling condoms and lubrication and the exploration of sexual negotiation strategies with potential partners.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were at the age at which sex and sexuality were important issues and they were aware of the difficulties that disclosure of their status might pose to potential partners. Receiving positive, encouraging and normalising messages about their sexuality and sexual behaviour is important in order that positive young people do not grow up with negative feelings about themselves, sex and sexuality (Fielden et al, 2006;Campbell et al, 2009). Interestingly, participants did not comment on the specific sexual health components of the LFP which included experience of handling condoms and lubrication and the exploration of sexual negotiation strategies with potential partners.…”
Section: Discussionmentioning
confidence: 99%
“…If the prognostic value of OC is present in HIV+/AIDS adolescents, it should be assessed. The pattern of the progression of HIV-infection in children and adolescents trends to behave as a chronic disease, and therefore their psychosocial needs resemble the needs of the chronically ill patients rather than the terminally ill ones (17). The increase of life expectancy observed in perinatally HIV-infected children and adolescents and the need to improve their quality of life will increase their demand of oral health services.…”
Section: E549mentioning
confidence: 99%
“…Canadian children who were HIV positive reported that they were reluctant to disclose their HIV status because they had experienced being ostracised, or anticipated losing friends (Fielden et al, 2006). This social stigma was also reported by Chinese children with leukaemia (Wu et al, 2010) and Taiwanese children with celebral palsy (Huang et al, 2009).…”
Section: What Are the Needs Of Children Who Have Life Limiting Illnesmentioning
confidence: 91%
“…Teachers might need to provide factual information a out a hild s ill ess to others in order to facilitate easier re-integration of a child back among his/her school peers (Gorin and McAuliffe, 2008) and to prevent stigmatisation (Fielden et al, 2006). Teachers also need to consider providing support for the siblings of children who are very sick (Breen et al, .…”
Section: What Are the Needs Of Teachers Who Are Teaching Children Witmentioning
confidence: 99%